OVERVIEW OF THE LEVEL OF INDEPENDENCE OF THE ELDERLY IN FULFILLMENT OF DAILY ACTIVITIES AT TRESNA SOCIAL HEALTH CENTER WERDHA NOBILITY JAMBI PROVINCE YEAR 2023 - Hanif, Hanif Riyeldi Ramadan; Kamariyah; Yusnilawati (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
The final stage of the aging process in human growth and development is a term for elderly. Elderly (elderly) is someone who has entered the age of 60 years and over. Increasing age causes changes in organ function cause impact to direction ability elderly For do Activities of Daily Living. Research This aiming For know description level independence elderly in fulfillment activity daily. Type study This use design descriptive quantitative. Study This done at the orphanage Social Tresna elderly (PSTW) Jambi Province. The total elderly population that there are 67 people in the Tresna Werdha Social Home (PSTW). Sampling was carried out with technique Total Sampling.Based on the level of independence of the elderly in carrying out daily activities, it was obtained The results in the independent category were 33 people (49.2%), light dependency 4 people (6%), dependence currently 16 person (23.8), dependence heavy 8 person (12%) And level dependence total namely 6 people (9%). The description of the level of independence of the elderly in carrying out daily activities is in the independent category there were 33 people (49.2%), consisting of 91.8% eating, bathing as much as 88%, neatness/appearance as much as 86.5%, get dressed as much as 83.5% And CHAPTER as much as 80.5%.